Character Values in the Film "Surau dan Silek" (A Semiotic Analysis of Charles Sanders Peirce) (Cinematology: Journal Anthology of Film and Television Studies, 2024)
This article discusses the character values contained in the film Surau dan Silek. The research method used is descriptive qualitative, employing Charles Sanders Peirce's semiotic analysis method. In his method, Peirce views the subject as an inseparable part of the signification process. Peirce's triadic model (representamen, object, interpretant, equivalent to the sign) shows the significant role of the subject in the process of language transformation. Peirce believed that signs have meanings that continuously evolve or undergo unlimited semiosis, which is the process of creating an endless chain of interpretants. This film is a cultural film in the Minangkabau language containing advice. The film tells the story of three Minangkabau teenagers who are excited about practicing silat, but they are left behind by their silat master, Mak Rustam, who decides to go abroad. This study finds the representation of character education in the film Surau dan Silek, where silat teaches the balance between emotional intelligence, spiritual intelligence, intellectual intelligence, and heart intelligence. The film Surau dan Silek contains many moral messages, religious values, and cultural insights, which help change the perception of silat in Minangkabau, not only as a youth activity for fighting, but also as a character education from the perspectives of Islam and Minangkabau customs. This includes practicing Islam as a teaching and preserving the culture of surau and silat as Minangkabau youth activities.